Leptospirosis Prevalence in a Population of Yucatan, Mexico. (2nd November 2011) - Joel, Navarrete Espinosa; Maribel, Moreno Muñoz; Beatriz, Rivas Sánchez; Oscar, Velasco Castrejón
Abstract : Objective . To measure the prevalence of leptospirosis with two techniques in inhabitants of Izamal, Yucatan and to determine its relation with some exposure factors. Material and Methods . Transversal study in populations belonging to the HR62—IMSS-Opportunities working force in Izamal, Yucatan. Population, including 6 years of age or more, was randomly selected to participate in the study. A questionnaire was applied for personal ID and exposure factors; blood samples were taken for leptospirosis diagnosis. Simple frequencies, proportions, tendency and dispersion measures, prevalence and odd ratios and confidence intervals (CI) of 95%, and logistic regression model were obtained. Results . 204 patients, between 9 and 80 years old were included; 180 were positive (88.2%) with the dark-field technique; using MAT cutoff at 1 : 40, 178 patients (87.3%) were positive, while at 1 : 80 there were 103 positive (50.5%). The predominant serovar was Hardjo (94%). The highest prevalence was in women (96.3%) and in the >45-year-old group (95.7%); feminine gender (RM = 2.31 IC 95% 3.59–28.6), housewife (RM = 22.8 IC 95% 4.9–106.1), being in contact with stagnant water (RM = 5.2 IC 95% 1.7–15.9), and being in contact with domestic animal feces (RM = 5.1 IC 95% 1.9–13.1), these being the most significant variables in the final logistic regression model. Conclusions . The prevalence found was higher than the one nationally and internationally reported, representing an important finding, being in turn a local public health, maybe nationally. It is urgent to reinforce this research as well as to establish preventive and control measure to avoid exposure and health damages.